GAMBARAN POLA MAKAN PADA IBU HAMIL DALAM MENCEGAH STUNTING: A SCOPING REVIEW - Lukman, Mamat; Sejati, Femmy; Pebrianti, Sandra (JURNAL KESEHATAN KARTIKA, 2023)
Background: Stunting is a chronic nutritional health problem in toddlers. However, stunting can prevent by maintaining maternal health during pregnancy,such as controlling diet and nutritional intake. Therefore, pregnant women are expected to control their diet. Method: : This study uses a scoping review method. The databases used are EBSCOhost and PubMed with relevant search studies published from 2017-2022. The inclusion criteria of the selected articles are English articles, full text articles. The excluded articles are articles that use meta-analysis and systematic review methods. Result: 8 articles passed the selection and it was found that there were seven articles showing the type and pattern of healthy eating significantly increasing birth weight which is an indicator of growth and stunting incidence. In detail, the types and patterns of healthy eating for pregnant women are increasing food intake by 15% from usual by consuming main meals 3x a day plus 2x snacks consisting of 5 types of food (MDD-W) with 4 servings/week in each types, so that the nutrition of pregnant women is still fulfilled, complited by multivitamin supplementation (vitamin B-1 (thiamin), B-2 (riboflavin), B-6, niacin, B-12, C, and E), calcium, folic acid and tablets IFA. Conclusion: The type and pattern of healthy eating in pregnant women produces a significant good effect on birth weight to prevent stunting. And demographic factors affect the diet of pregnant women. .